L'amour lointain de Jaufré Rudel et le sens de la poésie des troubadours - Spitzer, Leo, 1887-1960 (Book collections on Project MUSE., 1944)
Leo Spitzer, refuting ideas set forth by Grace Frank, redefines l'amour lointain as the result of the "paradox amoureux," which is the base of all troubadour poetry. This is a forty-four page article with extensive notes